THE Edukasi Manfaat Puasa bagi Kesehatan dalam Perspektif Medis pada Masyarakat Desa Rumak - Pauzan; Syamsuriansyah; Idham Halid; Ajeng Dian Pertiwi; Ika Nurfajri Mentari; Syahrul; Beny Binarto Budi Susilo; Muhammad Nawawi Muhamad Khalid Iswadi; Khairul Amri Assidiq; Sar’in (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2026)
Fasting is a form of religious practice that not only provides spiritual benefits but also has positive effects on human health. From a medical perspective, fasting plays an important role in improving metabolic function, enhancing the immune system, and helping prevent various degenerative diseases. This community service activity was conducted in Rumak Timur Selatan Hamlet, Rumak Village, Kediri District, West Lombok Regency, West Nusa Tenggara, with the aim of increasing public knowledge regarding the health benefits of fasting. The activities were carried out through health education sessions, healthy lifestyle counseling, and interactive discussions with the community. The results showed that the community demonstrated high enthusiasm and gained new understanding regarding the benefits of fasting for digestive health, blood sugar control, cardiovascular health, and improvement of the body’s immune system. This activity is expected to increase public awareness in adopting healthy lifestyles while observing fasting practices.